(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
The article examines the daily flight activity, speed, and return to the hive with pollen and nectar of Carpathian bee colonies fed with soy milk for 3 minutes during spring, summer, and autumn seasons, and draws relevant conclusions.